PENGARUH PROMOSI TERHADAP SIKAP PASIEN RS PKU MUHAMMADIYAH BANTUL - Susanto Susanto; Sari Dwi Astuti (Universitas Muhammadiyah Yogyakarta, 2013)
The mushrooming hospitals in Bantul had forced PKU Muhammadiyah hospital to conduct promotions. A promotion will be very useful to provide information to the society about the service excellence offered by a hospital in order that it becomes the society’s preference when they seek for medical and health treatment. This research was a descriptive quantitative one using cross sectional approach. The population included all outpatients, and the sample was confined to 90 patients. Meanwhile, the analytical tool was the multiple linier regression. This research found a regression equation of Y = 0.225 X1 + 0.267X3 + 0.338X4 + e. The coefficient of determination (R2) was 0.649, which explained that the involvement of promotion influenced patients’ attitude as much as 64.9%. The score of F count was 42.159 with F significance of 0.000 and 95% confidence. For the mean time, the influence of promotional activities to the attitude of the patients of PKU MuhammadiyahBantul Hospital comprised advertising (2.129, p = 0.036), direct marketing (2.774, p = 0.007), and public relation (3.657, p= 0.000). Meanwhile, the variable personal selling did not influence the patient’s attitude (1.074, p = 0.286). To sum up, the factors in promotion mix influencing the attitude of the patients in PKU MuhammadiyahBantul Hospital are advertising, direct marketing, and public relation.